The Effectiveness of Palm Oil Policies in Nigeria: An Experience from Malaysian Palm Oil Policies - Shehu, Sani (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2024)
The tropical forest of West Africa is initially the first area where the oil palm was discovered before the 14th century. In particular, Nigeria was one of the places where this fruit was uncovered. Palm oil is ranked as the major vegetable oil in the world. In the 1960s, Nigeria was rated as the largest palm oil-producing and exporting country globally. However, the production was completely unsuccessful as a result of the government’s failure to formulate good policies, while the local consumption increases. Oil palm production in Malaysia became a contributing sector to the national economy. It alleviates poverty, provides employment, allocates resources, generates incomes, and leads to economic development. Due to good and sustainable palm oil policies in this sector, Malaysia achieved global recognition. This paper’s objective is to disclose the ineffective policies on palm oil in Nigeria and its sustainability in Malaysia. This paper is a qualitative design, it used primary and secondary methods. The primary method is based on a semi-structured interview, while the secondary method is based on documents. It adopted inductive thematic analysis for analysing interview data with the help of Atlas ti. This paper’s finding is the unsuccessful palm oil policies in Nigeria and the sustainable palm oil policies in Malaysia.In conclusion, there is a need for Nigeria, to learn from the Malaysian experience.